ECONOMIC AND ORGANISATIONAL PROBLEMS OF PLANT PROTECTION IN ORCHARDS WITH INTEGRATED FRUIT PRODUCTION - Golinowska, Maria (Acta Scientiarum Polonorum. Oeconomia, 2002)
Summary. The Integrated Fruit Production (IPO) in the orchards of the southwestern Poland was introduced in 1994. The number of fruit-growers obtaining certificates of apple production by the IPO method was systematically growing. The method is consumer- and environment-friendly. The research has shown that introducing this system of fruit production brought about a decrease in the pesticide (especially insecticide) usage by 50% as well as a decrease in the frequency of chemical treatments by half. All the fruit-growers running the integrated fruit production were volunteers and received instruction on courses organized by the Institute of Fruit and Flower Production in Skierniewice. The fruit produced by means of the IFP method are more difficult to sell, while their sales depend to a large extent on the fruit-growers’ invention and marketing skills.